2011
DOI: 10.1128/jcm.00196-10
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Real-Time PCR Assay for Detecting and Quantifying Human Bocavirus 2

Abstract: Human bocavirus 2 (HBoV2) is a parvovirus that has been recently identified in stool samples from children. Any association between the virus and clinical disease is unclear. A rapid, reliable diagnostic method is necessary to address this issue. In this study, we developed a sensitive and specific HBoV2 quantitative real-time PCR assay that targets the HBoV2 NP-1 gene, based on the TaqMan method. The assay could reproducibly detect 10 copies of a recombinant DNA plasmid containing a partial region of the HBoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
2
16
0
4
Order By: Relevance
“…Furthermore, in our previous study there is no difference found in the sequence characteristics of HBoV2 between these case and control groups. 16 We developed the HBoV2 real-time PCR method and also detected low HBoV2 viral loads in children stool samples from Shanxi province in a previous study 15 which is in the same situation as in this study. The low HBoV2 viral loads suggest that this virus is not a causative agent of gastroenteritis.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, in our previous study there is no difference found in the sequence characteristics of HBoV2 between these case and control groups. 16 We developed the HBoV2 real-time PCR method and also detected low HBoV2 viral loads in children stool samples from Shanxi province in a previous study 15 which is in the same situation as in this study. The low HBoV2 viral loads suggest that this virus is not a causative agent of gastroenteritis.…”
Section: Discussionmentioning
confidence: 80%
“…Госпитализация при HBoV2 моноинфекции составляет, в среднем, 11,3 дня. Патогенность изолятов генотипа HBoV4 для че-ловека обсуждается [52,83].…”
Section: клинико-эпидемиологические особенности бокапарвовирусной инфunclassified
“…В Китае максимум заболеваемости отмечен в период с февраля по апрель [71,83]. В РФ бо-кавирусные инфекции диагностируются в те-чение всего года.…”
Section: клинико-эпидемиологические особенности бокапарвовирусной инфunclassified
See 2 more Smart Citations